A bioorthogonal system reveals antitumour immune function of pyroptosis - Qinyang Wang; Yupeng Wang; Jingjin Ding; Chunhong Wang; Xuehan Zhou; Wenqing Gao; Feng Shao; Zhibo Liu (Nature, 2020)
Bioorthogonal chemistry capable of operating in live animals is needed to investigate biological processes such as cell death and immunity. Recent studies have identified a gasdermin family of pore-forming proteins that executes inflammasome-dependent and -independent pyroptosis<a id="ref-link-section-d38956e507" href="https://www.nature.com/articles/s41586-020-2079-1#ref-CR1" title="Kayagaki, N. et al. Caspase-11 cleaves gasdermin D for non-canonical inflammasome signalling. Nature 526, 666–671 (2015)." data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">1,<a id="ref-link-section-d38956e507_1" href="https://www.nature.com/articles/s41586-020-2079-1#ref-CR2" title="Shi, J. et al. Cleavage of GSDMD by inflammatory caspases determines pyroptotic cell death. Nature 526, 660–665 (2015)." data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">2,<a id="ref-link-section-d38956e507_2" href="https://www.nature.com/articles/s41586-020-2079-1#ref-CR3" title=" gasdermin-mediated programmed necrotic cell death. Trends Biochem. Sci. 42, 245–254 (2017)." data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">3,<a id="ref-link-section-d38956e507_3" href="https://www.nature.com/articles/s41586-020-2079-1#ref-CR4" title="Wang, Y. et al. Chemotherapy drugs induce pyroptosis through caspase-3 cleavage of a gasdermin. Nature 547, 99–103 (2017)." data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">4,<a id="ref-link-section-d38956e510" href="https://www.nature.com/articles/s41586-020-2079-1#ref-CR5" title="//doi.org/10.1038/s41577-019-0228-2 (2019)." data-track="click" data-track-action="reference anchor" data-track-label="link" data-test="citation-ref">5. Pyroptosis is proinflammatory, but its effect on antitumour immunity is unknown. Here we establish a bioorthogonal chemical system, in which a cancer-imaging probe phenylalanine trifluoroborate (Phe-BF3) that can enter cells desilylates and ‘cleaves’ a designed linker that contains a silyl ether. This system enabled the controlled release of a drug from an antibody–drug conjugate in mice. When combined with nanoparticle-mediated delivery, desilylation catalysed by Phe-BF3 could release a client protein—including an active gasdermin—from a nanoparticle conjugate, selectively into tumour cells in mice. We applied this bioorthogonal system to gasdermin, which revealed that pyroptosis of less than 15% of tumour cells was sufficient to clear the entire 4T1 mammary tumour graft. The tumour regression was absent in immune-deficient mice or upon T cell depletion, and was correlated with augmented antitumour immune responses. The injection of a reduced, ineffective dose of nanoparticle-conjugated gasdermin along with Phe-BF3 sensitized 4T1 tumours to anti-PD1 therapy. Our bioorthogonal system based on Phe-BF3 desilylation is therefore a powerful tool for chemical biology; our application of this system suggests that pyroptosis-induced inflammation triggers robust antitumour immunity and can synergize with checkpoint blockade.